Evaluation of Senior High School Students’ Ability to Reading Chemistry Text - Arum Setyaningsih; Sri Rahayu; Parlan Parlan; Munzil Munzil; Wako Uriu (AL-ISHLAH: Jurnal Pendidikan, 2024)
Science text reading activities can introduce students to understanding chemical concepts and practice reading skills. Reading skills play an important role in science education because they are related to student's cognitive and metacognitive abilities. This study aims to see how the ability to read texts and students' understanding of chemical concepts through texts. This research uses a mixed method design, embedded type. Quantitative data is obtained through survey results and qualitative data is obtained through interviews to strengthen the justification of quantitative data obtained. Participants in this study were 299 high school students in the cities of Malang and Batu. The research instrument is an instrument of reading chemistry text skills (r = 0.918) consisting of 3 chemistry texts and in each of them, there are 8 essay questions covering literal, interpretation, and application aspects. The profile of students' reading skills based on the results of surveys and interviews shows that most students' reading skills have not been able to understand the idea of chemical concepts correctly, have not been able to describe chemical terms in the text correctly, students' explanations of chemical concepts are at the structural level, and have not been able to provide creative ideas (arguments) for solutions to problems presented in the text. The implications of this study need to be explicit skills in reading chemistry texts to understand chemical concepts and be proficient in reading chemistry texts.